Dancers at London's Italian Opera Houses as Recorded in the Libretti. (November 2015) - Burden, Michael
Abstract : For the audience, the purchase of a libretto when attending the King's Theatre, London's elite house for foreign opera and dance, was a commonplace. It offered the text of the opera, and a parallel English translation; it could also contain an argument for the opera, and other material relevant to the performance. A dramatis personae was nearly always included, together with a cast list, and after the mid-century, the libretti often contained the names of the dancers and choreographers. This article sets out to document the mentions of these names, and to chart their inclusion in the context of the history of the libretto. It identifies the first inclusion of a choreographer's name (in Antigono, in May 1746), the first dancers (in Ipermestra, in November 1754), and the first leader of the dancers (in the libretti for the 1790–1791 season), and identifies the inexplicable tailing off, and then total omission, of dancer personnel from the London Italian opera libretti.